Harvest: A Mobile Platform for Direct Farmer to Buyer Transactions (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study presents HARVEST, a mobile-based platform designed to facilitate direct farmer-to-buyer transactions and address inefficiencies in agricultural trading in Mabini, Pangasinan. Farmers in the area face challenges such as dependence on intermediaries, limited market access, and unstable pricing, which reduce income and increase costs for consumers. To address these issues, the system provides key features including product listing, direct messaging, order processing, and transaction monitoring, enabling more transparent and efficient trading. The platform was developed using a three-tier architecture and the Agile development methodology, incorporating continuous feedback from farmers, cooperatives, and the Municipal Agricultural Office to ensure usability and contextual relevance. System evaluation was conducted using the ISO/IEC 25010 Software Quality Model, with fourteen (14) respondents participating in the assessment. Results indicated an overall weighted mean of 4.27, interpreted as Excellent, reflecting high acceptability in terms of usability, performance efficiency, and reliability. The findings demonstrate that HARVEST improves market accessibility, enhances transaction efficiency, and reduces dependence on intermediaries. While the sample size is limited, the results provide initial evidence of the platform’s potential to support more transparent and sustainable agricultural trade. The study contributes to digital agriculture by presenting a localized and user-centered mobile solution tailored to rural farming communities.